Implementasi Program Atensi Permakanan Bagi Lanjut Usia Tunggal di Kecamatan Kembangbahu Kabupaten Lamongan (Studi Di Desa Lopang dan Desa Gintungan): (Studi Di Desa Lopang Dan Desa Gintungan) - Naila Ainaiya1; Indah Prabawati; Tjitjik Rahaju; Ahmad Nizar Hilmi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The increasing number of elderly individuals living alone as a vulnerable group requires effective policies to fulfill their basic needs, one of which is implemented through the Social Rehabilitation Assistance Program (ATENSI) for Food Support. This program is regulated under the Regulation of the Minister of Social Affairs Number 7 of 2021 and aims to assist vulnerable groups requiring social support. However, its implementation at the sub-district level still faces administrative challenges and limited facilities that may affect its effectiveness. This study aims to analyze the implementation of the ATENSI Food Support Program for elderly individuals living alone in Kembangbahu Sub-district, Lamongan Regency. The research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, and analyzed using policy implementation indicators: communication, resources, disposition, and bureaucratic structure. The results show that communication has been conducted hierarchically, although obstacles remain in information delivery and beneficiary understanding. Human resources are adequate, but facilities are limited. Implementers demonstrate commitment, and the bureaucratic structure supports coordination. Overall, the program has been implemented fairly well but still requires improvement in facilities and administrative simplification.